Pengaruh Komunikasi, Motivasi Kerja Dan Kompetensi Terhadap Kepuasan Kerja Serta Implikasinya Pada Kinerja Dosen Pada Perguruan Tinggi Pariwisata Swasta Di Jawa Barat - Riyadi, Heru; Utomo, Bambang Sapto; Masatip, Anwari (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
The background to this research isÂ based upon the phenomenon that is where lectures performances is not optimal so that the students' quality not favorable. As for the main factor, is the despicable performance of lecturer job satisfaction is low. Based on the previous researches, low job satisfaction is often caused by non-optimal of communication, work motivation and competences of lecturers at the private tourism college in west java. This study aims to acknowledge and analyze the impact of communication, work motivation and competences on job satisfaction and its implication on lecturers' performance in West Java private tourism college. This study uses a descriptive and explanatory survey approach. In this study, the samples were 224 lecturers in west java private colleges. The research used path analysis to interpret and explain the data result. The research concludes that there is an influence of the communication on job satisfaction of 3, 6%. Furthermore, the effect of work motivation on job satisfaction was 20, 3% and the effect of competences on job satisfaction were 12, 9%. In overall, the influence of independent variables on the job satisfaction was 70%, while the remaining 30% was from the other factors which were not examined for this research.